C4.5 Algorithm Classification for Determining Smart Indonesia Program Recipients at MIS Al-Khoirot - Weni Ratna Sari Oktapia Ningse; S Sumarno; Zulaini Masruro Nasution (Yayasan Literasi Sains Indonesia, 2022)
The purpose of the research is to assist the school in selecting student data as recipients of the PIP (Smart Indonesia Program) to be more objective and practical and to assist in increasing the accuracy of the targeting of the recipients of the PIP funds. In this study using Data Mining techniques using the C4.5 algorithm. The source of the research data used was obtained from observations and interviews with the MIS Al-Khoirot Tambun Nabolon Pematang Siantar school. The research variables used were parents' occupations, parents' income, KKS (Prosperous Family Card) holders, SKTM holders (Poor Certificate). In this study, the alternative used as a sample is the data of MIS Al-Khoirot students. The results of this study found that the most dominant attribute was the SKTM holder with a gain of 0.833764907, besides that this study produced 8 (eight) rules with an accuracy rate of 98.00%. Based on this, it can be concluded that the C4.5 algorithm can be used for the classification of the Determination of Smart Indonesia Program Recipients at MIS Al-Khoirot